Phoenix um framework para trabalhos em síntese de alto nível de circuitos digitais - Duarte, Flávio Luis (2006)
This work describes the development of an open framework for the synthesis of digital circuits, for use in hardware/software co-design projects. The framework consists of a compiler which accepts ANSI C as source code allowing the construction of a given system and its execution in hardware. This compiler, named Phoenix, allows great flexibility of use and easy expansion of its functionality. The compiler, besides its usual modules (scanning, parsing, code generation) builds graphs that describe data dependency, data control, flow and hierarchical dependency, essential information in order to generate and to explore parallel execution of code. The compiler generates code for execution in Nios II&#8482Altera Corporation "virtual" processor through retargetable code generation. Data structures built with the C language struct constructor are automatic supported for high-level synthesis of digital circuits.